The East India Company : corrupt governance and cruelty in India, 1806-1814. - Minto, Gilbert Elliot, Earl of, 1751-1814 (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2015)
The First Earl of Minto, Sir Gilbert Elliot Murray Kynynmound, served as Governor-General of India from 1806-1813. This collection is drawn from his personal papers during his time as premier of the East India Company (EIC), with extensive correspondence with other officials, papers from the political department, papers from the secret department, and files pertaining to his time as President of the Board of Control. Overall, the collection offers a top-down perspective on the brutal rule of the East India Company during the early 19th century. The East India Company was expanding its quasi-colonial ambitions into the Indian subcontinent, having first established governance of the wealthy Bengal region in the late 18th century. The rule of the EIC during these years was characterised by corruption, cruelty and exploitation of the native population and natural resources of the Indian subcontinent. Officials of the EIC aggressively extracted and plundered revenue and their policies exacerbated rural poverty and famine throughout the region. The resentment fostered during these years led directly to the Indian Rebellion of 1857, which then led to Britain assuming direct colonial control of modern day India and Pakistan.
Date range: 1806-1814.
Keywords: Minto, Gilbert Elliot, -- Earl of, -- 1751-1814 -- Correspondence; India -- Politics and government -- 1765-1947.